Penerapan pendekatan teori belajar Bruner untuk meningkatkan prestasi belajar penjumlahan dan pengurangan bilangan cacah pada tema benda, hewan dan tanaman di sekitarku bagi siswa sekolah dasar - Malaiswatiningsih Malaiswatiningsih (Universitas Sebelas Maret, 2020)
Abstract: The purpose of this Class Room Research is to increase the mathematic learning achievement about number summation and reduction on the IA students of 2 Leteh Elementary School on the Second Semester of the 2017/2018 Year Academic. The type of of this is the Kemmis and Mc Taggart’s Spiral Model, consist of planning, action, observation and reflection. The subjects of this research are the IA students of 2 Leteh Elementary School, as much as 30 students, consist of 12 boys and 18 girls. This research is consist of two cycles, each cycle consist of two meetings. Technique of collecting data of this research is using test technique. Technique of analyzing data of this research is using quantitative descriptive. The result of this research showed that the mathematic learning achievement on cognitive domain increased according with the average and completeness. The average on the pre cycle is 71, onthe first cycle is 71 and on the second cycle is 86, whereas the completeness on the pre cycle is 53% (16 students achieve the passing grade), then increase up to 14% on the first cycle become 67% (20 students achieve the passing grade) and increase up to 16% on the second cycle from 67% become 83% (25 students achieve the passing grade).Keywords: Bruner Learning Theory, Learning Achievement, Count Numbers.